2020
DOI: 10.18844/gjbem.v10i1.4540
|View full text |Cite
|
Sign up to set email alerts
|

Do Psychological Capital and Communication Skills Affect Entrepreneurial Intention?

Abstract: The purpose of this study was to demonstrate whether students' perception of psychological capital and their communication skills have an impact on their entrepreneurial intention. According to the results obtained from 369 undergraduates, who are study at a public university in Turkey, it was observed that there were positive relationships between their communication skills, psychological capitals and entrepreneurial intentions. Also, results indicated that psychological capital affects entrepreneuria… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 8 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…The phenomenon of entrepreneurship has been expressed in context of entrepreneur's relationship with organization or firms to meet goals, role in development of firms, management growth and transition (Yalap, Yılmaz & Polatçı, 2020). It has been observed that entrepreneurial progression plays a significant role in strategic growth in any business or corporate entity (Umrani, Mahmood, & Ahmed, 2016).…”
Section: Objective Of the Studymentioning
confidence: 99%
“…The phenomenon of entrepreneurship has been expressed in context of entrepreneur's relationship with organization or firms to meet goals, role in development of firms, management growth and transition (Yalap, Yılmaz & Polatçı, 2020). It has been observed that entrepreneurial progression plays a significant role in strategic growth in any business or corporate entity (Umrani, Mahmood, & Ahmed, 2016).…”
Section: Objective Of the Studymentioning
confidence: 99%
“…1.1 Review of related resources Communication (from Latin -making common, connecting, communicating) is a semantic aspect of social interaction. Since every individual action is carried out in terms of direct or indirect relationships with other people, it includes (along with the physical) the communicative aspect (Yalap & PolatÃ, 2020). Actions that are consciously focused on the meaning of their perception by other people are sometimes called communicative actions.…”
Section: Introductionmentioning
confidence: 99%
“…Because academic attitude and perceptual behavioral control are significantly influenced by psychological capital, a study conducted by Contreras et al (2017) on the relationship between psychological capital and entrepreneurial intents found that entrepreneurial intents are correlated with the dimensions of psychological capital. It has been shown that a positive effect exists in the interaction between psychological capital and entrepreneurial intent ( Yalap et al, 2020 ) and that psychological capital has a significant impact on entrepreneurial intents through traditional financial, human, and social capital ( Zhao et al, 2020 ). Both startup capital and psychological capital are important predictors of entrepreneurial success, but psychological capital is a better predictor ( Baluku et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%